Genetic characterization of coat color genes in Brazilian Crioula sheep from a conservation nucleus - Cavalcanti, Lilian Cristina Gomes; Moraes, José Carlos Ferrugem; Faria, Danielle Asis de; McManus, Concepta Margaret; Nepomuceno, Alcebiades Renato; Souza, Carlos José Hoff de; Caetano, Alexandre Rodrigues; Paiva, Samuel Rezende (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to identify single nucleotide polymorphisms (SNPs) in resequencing data from MC1R, ASIP, and TYRP1 genes derived from Crioula sheep (Ovis aris) with different coat colors. Polymorphisms in the ASIP (agouti-signaling protein), MC1R (melanocortin 1 receptor), and TRYP1 (tyrosinase-related protein 1) genes were analyzed in 115 sheep from Embrapa’s conservation nucleus of crioula sheep, in Brazil. A total of 7,914 bp were sequenced per animal, and 14 SNPs were identified. Two additional assays were performed to detect duplications and deletions in the ASIP gene. Ninety-five percent of the coat color variation was explained by epistatic interactions observed between specific alleles in the MC1R and ASIP genes. Evidence suggests an important role of TYRP1 variants for wool color, despite their low frequencies. The marker panel was efficient enough in predicting coat color in the studied animals and, therefore, can be used to implement a marker-assisted selection program in the conservation nucleus of sheep of the crioula breed.